Performance Outcomes after Surgical Repair of Achilles Tendon Rupture in the Women’s National Basketball Association - Amiethab A. Aiyer MD; Blake H. Hodgens; Joseph S. Geller; Michael G. Rizzo; Julianne Munoz; Jonathan R. Kaplan MD (Foot & Ankle Orthopaedics, 2022)
Category: Sports; Ankle Introduction/Purpose: Achilles tendon ruptures are devastating injuries in elite athletes. Current literature shows poor prognosis following Achilles tendon rupture in professional male basketball players, however there are currently no studies examining the effects of Achilles tendon rupture on performance outcomes in the Women's National Basketball Association (WNBA). Understanding the impact Achilles tendon rupture has on return to play and performance metrics in the WNBA will provide valuable information to players, team personnel, and medical professionals on post-injury expectations. Methods: 17 WNBA players who sustained an Achilles tendon rupture from 2000-2019 were identified from publicly available injury reports and player profiles. Demographic information collected included age, body mass index (BMI), position, and service in the WNBA when the tear occurred. Statistics were collected for the season before the injury, and two seasons after the injury, and the Player Efficiency Rating (PER) was calculated. PER is defined as ([points + rebounds + assists + steals + blocks] - [(field goals attempted - field goals made) + (free throws attempted - free throws made) + turnovers]) / games. Controls were matched by service in the WNBA, position, and PER. Results: Following Achilles tendon rupture, four players never returned to play in the WNBA, while seven players failed to play >1 season. Players who returned saw a significant decrease in the number of minutes played per game in both their first and second seasons post-injury (mean differences -6.11 and -6.54, respectively, p<0.01). Players also suffered a significant decrease in PER during their second season after injury compared with their pre-injury PER (mean difference -2.53, p=0.024). Compared to healthy controls, players who returned to play were significantly more likely to experience a decrease in minutes played per game at both one and two seasons postoperatively (-6.11 mpg vs +1.05 mpg, p<0.01 and -6.54 mpg vs +0.53 mpg, p= 0.018, respectively), while also experiencing significant per-game decreases in field goals (-0.85 vs + 0.20, p=0.47), free throws (-1.04 vs +0.12, p<0.01), steals (-0.48 vs +0.24, p=0.018), and points scored (-2.89 vs +0.58, p=0.014). Conclusion: Achilles tendon rupture and subsequent surgical repair in the Women's National Basketball Association (WNBA) accounted for significantly decreased minutes played and performance outcomes in athletes at one and two years post-operatively compared to both their pre-injury year and healthy matched controls. 23.5% of players failed to return to the WNBA, while 41.2% failed to play >1 season after returning from injury.